"Pingado Dilemma": Is formal contract sweet enough?. (August 2017) - Watanabe, Kassia; Bánkuti, Sandra Schiavi; Lourenzani, Ana Elisa
Abstract: "Pingado" is a Brazilian beverage similar to cappuccino, macchiato. For a good "pingado", coffee and milk should be of good quality. The formal institutions ensure the minimum attributes of quality for coffee and for milk in Brazil. However, in order to reach consumer desirable quality attributes for a differentiated "pingado" the transactions between farmers and agroindustry in quality-driven systems is likely to be conducted with hybrid forms. Thus, "Pingado Dilemma" involves the interactions between private and public institutions affect the combination of formal and informal governance mechanisms in transactions, in both chains, and involve complexities in terms of obligations to do and obligations to give in contract farming. This paper aims at analyzing the contract farming and the role of public and private institutions in transactions between farmers and agroindustry in Brazilian high-quality dairy and coffee chains. The research design used in this study is a case study based on multiple cases. The results indicate that while in dairy chain the private institutions reinforce public requirements (formal institutions), for the coffee sector, the role of private institutions is to establish and guarantee a new level of quality and differentiation. Interactions between private and public institutions affect the combination of formal and informal governance mechanisms in transactions, in both chains, and involve complexities in terms of obligations to do and obligations to give in contract farming. Highlights: Informal institutions complement formal institutions. Complex contract involves "obligation to give" and "obligations to do". The parties are autonomous and interdependent when contracts have asset specificity.